Rural Environmental Characteristics: A Case Study of the Selected Central Himalayan Villages - Joshi, R.C.; Reza, Masoom (National Geographical Journal of India, 2022)
Biotic and abiotic components co-exist systematically and are mutually interdependent having a bearing on the quality of life of the inhabitants. Less modern infrastructure, dependence on the agriculture and symbiotic relationships with nature are typical rural environment characteristics. Rural characteristics and their spatial variation are influenced by physiography for example in the study area agriculture crop production varies because of physiographic and micro climatic conditions. The variations can be perceived on the basis of their tone of language due to change in their physical landscape. In mountainous area it is common saying that in every 10-20 minutes' walk of distance there is change in the language. Village Information System (VIS) is a process which incorporates the spatial and non-spatial information of a village in a GIS platform for this work ten villages are selected from the Outer and Lesser Himalayan domain. Using collected information from satellite data, census 2011 and field survey, a detailed analysis is carried out i.e. landuse/cover (LULC), soil characteristics, rainfall, spring water discharge, road and other infrastructural facilities have been collected. Socio-economic survey of each household is also conducted. All collected information is stored in a digital cadastral layer using GIS technique. This work is very important for planning and management of village resources and creation of infrastructure for the sustainable development.